The role of hypoxia-inducible factors in tumor angiogenesis and cell metabolism - Xiu Lv; Jincheng Li; Chuhong Zhang; Tian Hu; Sai Li; Sha He; Hanxing Yan; Yixi Tan; Mingsheng Lei; Meiling Wen; Jianhong Zuo (Genes and Diseases, 2017)
Hypoxia-inducible factor (HIF) is a main heterodimeric transcription factor that regulates the cellular adaptive response to hypoxia by stimulating the transcription of a series of hypoxia-inducible genes. HIF is frequently upregulated in solid tumors, and the overexpression of HIF can promote tumor progression or aggressiveness by blood vessel architecture and altering cellular metabolism. In this review, we focused on the pivotal role of HIF in tumor angiogenesis and energy metabolism. Furthermore, we also emphasized the possibility of HIF pathway as a potential therapeutic target in cancer.